2014
DOI: 10.1186/preaccept-1205136964127976
|View full text |Cite
|
Sign up to set email alerts
|

Temperature during larval development and adult maintenance influences the survival of Anopheles gambiae s.s.

Abstract: Background: Malaria transmission depends on vector life-history parameters and population dynamics, and particularly on the survival of adult Anopheles mosquitoes. These dynamics are sensitive to climatic and environmental factors, and temperature is a particularly important driver. Data currently exist on the influence of constant and fluctuating adult environmental temperature on adult Anopheles gambiae s.s. survival and on the effect of larval environmental temperature on larval survival, but none on how la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…In contrast, in areas of unstable transmission, where malaria is seasonal, availability of mosquito breeding habitat in the dry season is one of the limiting factors for malaria transmission. Rainfall has been indicated as major determinant that limits the length of malaria transmission to the wet season in semi-arid areas [ 39 ]. In such cases, reservoirs may effectively create conditions suitable for mosquito development as they increase humidity throughout the year, thereby increasing vector abundance at times of year when they would not normally be found.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in areas of unstable transmission, where malaria is seasonal, availability of mosquito breeding habitat in the dry season is one of the limiting factors for malaria transmission. Rainfall has been indicated as major determinant that limits the length of malaria transmission to the wet season in semi-arid areas [ 39 ]. In such cases, reservoirs may effectively create conditions suitable for mosquito development as they increase humidity throughout the year, thereby increasing vector abundance at times of year when they would not normally be found.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in temperature can profoundly impact mosquito population dynamics [11], mosquito life history traits [1218], mosquito immune responses [1922]), and measures of parasite / pathogen fitness (prevalence, titers, and the extrinsic incubation period) [1, 10, 23, 24]. In addition to environmental temperature, variation in precipitation [25–27] and relative humidity [28] also drive vector-borne disease transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we demonstrated that the larval breeding habitats in the three sites vary distinctly with regard to their physico-chemical characteristics and microbial abundance. Previous studies have demonstrated that the physico-chemical characteristics [30][31][32] of the larval breeding habitat determine the larval and pupal density, the size and number of emerged adults and the survival of both larvae and adult mosquitoes. Thus, the mosquitoes in the study sites could also differ in their fitness (e.g.…”
Section: Discussionmentioning
confidence: 99%